Induction of gametocytogenesis in human malaria parasites: from stress to genome editing - Subramaniam, Rishitharan; Chiew, Zi Yan; Zuhaidi, Nabel Darwish binti; Lau, Yee Ling; Cheong, Fei Wen (Frontiers in Microbiology, 2025)
Gametocytogenesis is a crucial process in which malaria parasites transition from their asexual stage to the sexual-stage gametocytes. This transformation enables the parasite to infect and multiply within the Anopheles mosquito, the vector responsible for transmitting the disease between hosts. Understanding how gametocytogenesis works and how it can be controlled offer insights into the malaria life cycle and potential strategies for controlling the transmission. Significant efforts have been dedicated to gametocytogenesis induction in the laboratory using in vitro parasite cultures over the past few decades. This mini review aims to summarize the various gametocytogenesis induction methods employed thus far in human Plasmodium species, moving from conventional means of environmental stressors to the cutting-edge technology of genome editing to achieve precise modifications on various sexual conversion-related genes. While massive strides have been made in both domains of gametocytogenesis induction methods, the scalability of gametocytogenesis induction leaves much to be desired, especially for non falciparum species. In conclusion, integrating knowledge from both approaches is crucial to developing highly efficient methods for inducing gametocytogenesis in Plasmodium spp. This integration can enhance our understanding of the processes involved in gametocytogenesis and support the search for novel strategies with potential implications for malaria control and eradication.